Rozhodování a rozhodovací procesy v ošetřovatelství - Festová, Andrea; Bártlová, Sylva (Ošetrovateľstvo, 2015)
Background: Review article points out the importance of nurses in the decision-making process, which is an important part of the cognitive activities of a nurse and is one of the main skills of characterizing the professional nursing. The Declaration of the conference in Vienna in 1988 states that the role of the nurse is that it has to act as a partner in decision-making and planning (WHO, 1997). Objective: The main aim is to definine the decision-making process and decision-making in nursing. On these bases, describe the factors influencing decision-making in nursing, barriers to decision-making for nurses and also the importance of participatory decision-making. Methods: The contained theoretical bases are the result of the analysis of monographs, periodicals and legislative documents. Via the special keywords have been searching monographic resources and articles in scientific databases and then these articles were then subjected to content analysis. Results: The decision and decision-making process in nursing were defined. The factors influencing decision-making process in nursing and also the barriers in nursing decision-making process have been described. Due to the nature of nurse´s work the importance of participatory decision-making process have been also described. Conclusion: In the context of the provided care, nurse has to make numbers of decisions. The decision-making processes in nursing are influenced by many factors. But ultimately, they always affect patients care.
Keywords: profesionální nezávislost; lidé; klinické kompetence; Nurses; Professional Autonomy; Clinical Competence; Nursing Care; ošetřovatelská péče; rozhodování; zdravotní sestry; Decision Making; Humans